Effects of Knowledge Channel videos on the achievement of students in various learning environments - Gustilo, Leah E. (Animo Repository, 2015)
This study, which was part of a larger data gathered in 2014, utilized an experimental research design to investigate whether students from three learning environments (Passive, Active, Lecture) will have significantly different gains in terms of achievement test scores. Students in the passive learning environment were simply made to watch Knowledge Channel (KC) videos. Students in the active learning environment watched KC videos with the teacher facilitating the processing of the contents of the video. Students in the lecture learning environment were taught using the transmissive lecture mode of instruction without using the KC videos. For each school, five subject areas (English, Math, Science, Filipino and Social Studies) were included. A total of 926 students participated in this study and these students were randomly assigned to each of the three learning environments. A 15-item achievement test for each subject area was developed. To compare the mean scores of students across the three learning environments, independent samples t-test and factorial ANOVA were employed. Results revealed that the mean gain scores foreach of the learning environments yielded significantly positive results, with posttest scores > pretest scores. Students in the Active learning environment had the highest gain score, with the use of KC videos with teachers’ processing accounting for the 74.15% increase in the students’ posttest scores. Post-hoc analysis of pairwise comparisons show that there is significant difference between the gain scores of the students in the Active learning environment and the gain scores of the students in either the Passive or the Lecture learning environment. © 2015 American Scientific Publishers.